Alkyl‐Amino Functionalized Reduced‐Graphene‐Oxide–heptadecan‐9‐amine‐Based Spin‐Coated Microsupercapacitors for On‐Chip Low Power Electronics. Issue 2 (1st December 2021) - Vyas, Agin; Zare Hajibagher, Simin; Mendez Romero, Ulises; Azega, R. K.; Wang, Ergang; Lundgren, Per; Enoksson, Peter; Smith, Anderson D.
Abstract : With the miniaturization of microelectronics, integrated circuits can benefit from an on‐chip solid‐state power supply. Microsupercapacitors (MSCs), owing to their long lifetimes and complementary metal‐oxide‐semiconductor (CMOS) compatible fabrication, can be a potential on‐chip energy storage unit. MSCs fabricated through spin coating graphene‐oxide (GrO) often suffer from insufficient electrode thicknesses that lead to low energy densities. It, therefore, requires functionalizations for GrO that can improve the MSC electrode thickness and, thereby, the performance of the MSC. Thus, herein, the MSCs fabricated of alkyl‐amino functionalized reduced‐graphene‐oxide–heptadecan‐9‐amine (rGO) are reported for enhanced electrode thickness, high capacitance, and lower series resistance compared with functionalized GrO‐based MSCs (GO‐MSCs). The functionalized rGO solves a significant issue of inadequate electrode thickness in wafer‐scale MSC fabrication while achieving higher energy densities in fewer spin coatings. The rGO‐MSC displays an areal capacitance of 108 μF cm −2 compared with 24 μF cm −2 for the GO‐MSC while also demonstrating more than twice its power density in an integration compatible ionic liquid electrolyte 1‐ethyl‐3‐methylimidazolium bis(trifluoromethylsulfony)imide (EMIM‐TFSI). Abstract : Integrated circuits can benefit from microsupercapacitors (MSCs), a potential form of on‐chip power supply. MSCs fabricated through spin coating graphene oxide often suffer from insufficient electrode thicknesses that lead to low energy densities. This paper reports on MSCs fabricated of alkyl‐amino functionalized reduced‐graphene‐oxide–heptadecan‐9‐amine for enhanced electrode thickness, high capacitance, energy and power densities.